The fouling potential of colloidal silica and humic acid and their mixtures - Taheri, Amir Hooshang (2013)
The fouling propensity of an inorganic colloid (silica) and an organic (humic acid) and their mixture was studied in this paper. Fouling propensity was characterized as the modified fouling index (MFIUF) and specific cake resistance in dead-end UF at constant pressure. Experimental results for individual foulants demonstrated that MFIUF increased linearly with increasing particle concentration for both humic acid and colloidal silica over most of the concentration range, with deviations at the lowest concentrations. In terms of specific cake resistance, the individual foulants tended to have higher values at low concentrations that gradually declined to steady values at higher concentrations. These trends could be due to differences in cake formation and packing density with foulant flux. For the mixed foulants the presence of modest amounts of humic acid (<15 mg/L) tended to reduce both MFIUF and specific resistance below that of the colloidal silica alone (50–150 mg/L). This is attributed to the effect of the humic acid on silica packing density. At higher concentrations of humic acid (>20 mg/L) or lower concentrations of silica the mixture MFIUF started to exceed that of the colloid alone, possibly due to interstitial humic acid effects on cake resistance. Very low adsorption of humic acid on colloidal silica was also observed using Quartz crystal microbalance with dissipation (QCM-D) and zeta potential measurements. The results confirm that knowledge of the individual MFIUFs could not be used reliably to predict the fouling potential of the mixture.